Acute submaximal exercise does not impact aspects of cognition and BDNF in people with spinal cord injury: A pilot study - Keegan Nhan; Kendra R. Todd; Kendra R. Todd; Garett S. Jackson; Jan W. Van der Scheer; Gabriel U. Dix; Kathleen A. Martin Ginis; Kathleen A. Martin Ginis; Kathleen A. Martin Ginis; Kathleen A. Martin Ginis; Jonathan P. Little; Jeremy J. Walsh; et al. (Frontiers Media S.A., 2022)
ObjectiveTo investigate the effect of acute submaximal exercise, based on the spinal cord injury (SCI) Exercise Guidelines, on cognition and brain-derived neurotrophic factor (BDNF) in people with SCI.DesignEight adults (7 males) with traumatic SCI volunteered in this pre-registered pilot study. In randomized order, participants completed submaximal intensity arm cycling (60% of measured peak-power output at 55-60 rpm) for 30 min or time-matched quiet rest (control condition) on separate days. Blood-borne BDNF was measured in serum and plasma at pre-intervention, 0 min and 90 min post-intervention. Cognition was assessed using the Stroop Test and Task-Switching Test on an electronic tablet pre- and 10 min post-intervention.ResultsSubmaximal exercise had no effect on plasma [F(2,12) = 1.09; P = 0.365; η² = 0.069] or serum BDNF [F(2,12) = 0.507; P = 0.614; η² = 0.024] at either 0 min or 90 min post-intervention. Similarly, there was no impact of exercise on either Stroop [F(1,7) = 2.05; P = 0.195; η² = 0.065] or Task-Switching performance [F(1,7) = 0.016; P = 0.903; η² < 0.001] compared to the control condition. Interestingly, there was a positive correlation between years since injury and resting levels of both plasma (r = 0.831; P = 0.011) and serum BDNF (r = 0.799; P = 0.023). However, there was not relationship between years since injury and the BDNF response to exercise.ConclusionsAcute guideline-based exercise did not increase BDNF or improve aspects of cognition in persons with SCI. This work establishes a foundation for continued investigations of exercise as a therapeutic approach to promoting brain health among persons with SCI.